Deyeuxia himalaica (Poaceae, Agrostidinae): taxonomy and its first record from Myanmar - Paszko, Beata (Phytotaxa, 2014)
Deyeuxia himalaica, one of the rarest of the species of Deyeuxia known from southeastern Xizang, has been recorded for the first time on Myanmar’s Irriwaddy Plateau. The species’ taxonomy is clarified and discussed, especially in relation to the similar D. scabrescens. An amended diagnosis and description are provided.